“Green Products a Myth or Worth: An Indian Consumer Perspective” - Dhanwani, Neelam; Jainani, Kirti; Ojha, Nupur (International Journal of Psychosocial Rehabilitation, 2020)
According to sustainability goals of the United nation's everyone on the globe is concerned about environmental friendly practices in the Retail industry, especially for products designing, packaging, consumption, mode of advertising and so on. This study is an attempt to focus on these research questions: Firstly, How Indian Consumers are influenced to use green products? Secondly, Suggesting the suitable policy measures to increase green purchase in India. This is a conceptual paper to reviewvarious researchers findings on consumers perception or understanding the buying behaviour of Indian consumers and also with this article author(s) emphasized on finding critical factors that lead to purchase decisions by referring to existing literature review from year (2005 to 2019) . Secondary data is used in this study from various authentic sources like scopus indexed journals, UGC care listed journals, central government data and published news reports of UN conferences and Global seminars. Significance of this study is to determine the Indian mindset towards green consumption and also finding the critical factors influencing the purchase decision. To achieve sustainable growth, it is very important for the citizens of every country to follow the green practices.